Factors Influencing Dating Experiences Among African American Emerging Adults. (September 2014) - Hall, Naomi M.; Lee, Anna K.; Witherspoon, Daphne D.
This study examined sociocultural factors that impact dating and sexual experiences of heterosexual African American undergraduate college students attending a historically Black institution in the Southeastern United States. Specifically, mate availability and relationship involvement were analyzed to document students' experiences, and how these influences may be associated with sexual decision making and behavior. Data from nine focus groups ( N = 57) were aggregated and four subthemes were identified: competition among women, acceptability of mates, high prevalence of casual relationships, and lowered expectations for commitment. Power dynamics emerged as a contributing factor to the types of relationship involvement, sexual decision-making, and behavior among participants. The importance of prevention programs focusing on situational and cultural variables is highlighted. Additionally, implications for professionals working with emerging adults to consider the impact of the gender ratio imbalance, and perceived power distributions on perceptions of dating relationships, and sexual decision making and behavior are addressed.